The Relation between Reading Habits and Studets' Writing Ability at PBI UMY - Denny Irdantie Tikasari (PBI 14 UMY 002, 2014)
As one of the four main English language skills, writing plays an important role in the English language learning. However, writing is considered as a productive skill which has some difficulties in its process. Reading as a receptive skill is simply assumed to be one of the various ways for learners to improve their writing ability. Thus, the researcher is interested in finding out how the studentsâ€™ reading habits are. Besides, the investigation on the studentsâ€™ writing ability is also conducted through the studentsâ€™ Academic Reading and Writing score. The result on the studentsâ€™ reading habits and students score were important to discover the third research question on the relation between reading English text habit and studentsâ€™ writing ability at PBI UMY. The quantitative correlational research was employed to answer the research questions. A hundred PBIâ€™s students of academic year 2013/2014 become the respondents of this research. There are two variables in this research. The first variable is studentsâ€™ reading habits which are considered as independent variable. The second one is studentsâ€™ score as the independent variable. The instruments of this research are the closed-ended and open-ended questionnaire. The studentsâ€™ reading habits being investigated in order to answer the first research question is indicated by the three aspects namely the types of reading materials, the frequency of reading and the techniques of reading. The result shows that in terms of the types of reading materials, most of the students prefer to read the reference materials. In terms of frequency of reading, most of the students prefer to spend more time to read for general interest articles. Besides, in terms of the techniques of reading the students prefer to apply quick reading techniques while reading. The result of the second research question reveals that the level of studentsâ€™ Academic Reading and Writing score is in good category. The last result on the relation between studentsâ€™ reading habits and their writing ability shows that studentsâ€™ reading habits positively correlate with their writing ability in a weak level (r = 0.102). Therefore, the hypothesis alternative (H1) â€œthere is a positive correlation between studentsâ€™ reading habits and their writing ability in PBI UMYâ€ is accepted and the null hypothesis (H0) is rejected. Keywords: reading, writing, the relation between reading habits and studentsâ€™ writing ability.